Kemampuan Beberapa Spesies Jamur Tanah dalam Mengendalikan Globodera rostochiensis (Woll.) pada Tanaman Kentang - Kalay, Agusthin Marthin; Natasasmita, Sadeli; Suganda, Tarkus; Simarmata, Tualar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
Potatos cyst nematode (Globodera rostochiensis Woll.) in Indonesia has been find for the first time in Malang EastJava. This nematode suppress potato growth and caused yield looses up to 70.63%. Examination the ability of soilfungus Fusarium oxysporum TR1, F. solani TR2, F. oxysporum KT1, F. chlamydosporum KT2, F. oxysporum SM1,Paecilomyces lilacinus SM3, and F. chlamydosporum SM4 dalam pengendalian G. rostochiensis againsit G.rostochiensis on susceptible potato has been carried in out the green house, using Randomized Block Design withfour replication. Results showed that all of the seven fungi had the capacity to parasite G. rostochiensis. Inoculationof P. lilacinus SM3, F. chlamydosporum SM4, F. oxysporum KT1, and F. oxysporum SM1 decreased female populationto 58.56%, 59.09%, 60.76%, and 61.01% respectively compared to that without inoculation. While the other fungionly decrease female population up to 50%. The impact of male population reduction was the enhancement oftuber weight of potato. Adult male nematode was not found in this experiment.